Assessment of Lewis‐Acidic Surface Sites Using Tetrahydrofuran as a Suitable and Smart Probe Molecule. Issue 3 (24th March 2022) - Halawy, Samih A.; Osman, Ahmed I.; Abdelkader, Adel; Nasr, Mahmoud; Rooney, David W.
Abstract: Measuring the Lewis‐acidic surface sites in catalysis is problematic when the material's surface area is very low (SBET ≤1 m 2  ⋅ g −1 ). For the first time, a quantitative assessment of total acidic surface sites of very small surface area catalysts (MoO3 as pure and mixed with 5–30 % CdO (wt/wt), as well as CdO for comparison) was performed using a smart new probe molecule, tetrahydrofuran (THF). The results were nearly identical compared to using another commonly used probe molecule, pyridine. This audition is based on the limited values of the surface area of these samples that likely require a relatively moderate basic molecule as THF with p K b =16.08, rather than strong basic molecules such as NH3 (p K b =4.75) or pyridine (p K b =8.77). We propose mechanisms for the interaction of vapour phase molecules of THF with the Lewis‐cationic Mo and Cd atoms of these catalysts. Besides, dehydration of isopropyl alcohol was used as a probe reaction to investigate the catalytic activity of these catalysts to further support our findings in the case of THF in a temperature range of 175–300 °C. A good agreement between the obtained data of sample MoO3 ‐10 % CdO, which is characterised by the highest surface area value, the population of Lewis‐acidic sites and % selectivity of propylene at all the applied reaction temperatures was found. Abstract : Measuring Lewis‐acidic surface sites in catalysis is problematic when the material's surface area is very low (SBET ≤1 m 2  ⋅ g −1 ). For the first time, a quantitative assessment of total acidic surface sites of small surface area catalysts was performed using a new probe molecule, tetrahydrofuran. The results were nearly identical when compared to other commonly used probe molecule, pyridine. This work may be considered ground‐breaking in this field by applying the temperature‐programmed desorption (TPD) technique using both thermogravimetric (TG) and differential scanning calorimetry (DSC) analyses.